Prevalence of Psychological Disorders in Patients with Alopecia Areata in Comparison with Normal Subjects. (9th March 2014) - Aghaei, Shahin; Saki, Nasrin; Daneshmand, Ehsan; Kardeh, Bahare
Abstract : Alopecia areata is a chronic disease with a great impact on the patient's quality of life. In this study we reviewed the frequency of psychological disorders in patients with alopecia areata in comparison to a control group. We enrolled 40 patients with alopecia areata and a 40-volunteer random age-sex matched control group. The study is based on anxiety and Beck Depression Inventory (BDI) and the Eysenck Personality Questionnaire (EPQ). Analytical evaluation was done by Mann-Whitney, Kruskal Wallis, andt -tests. There was a significant difference between the case and control group regarding the prevalence of depression (P value = 0.008), anxiety (P value = 0.003), and neuroticism (P value = 0.05). There was no significant differences regarding extraversion (P value = 0.249), psychosis (P value = 0.147), and lying (P value = 0.899) between the two groups. In alopecia areata involving the head, there was a significant relation only between neuroticism (P value = 0.045) and lying (P value = 0.005). The facial involvement had a significant relation with depression (P value = 0.020), anxiety (P value = 0.019), and neuroticism (P value = 0.029). The frequency of psychological disorders in the case group is significantly greater than the control group.